The relationship between non-formal education, formal education and the private sector in a system for the provision of education for the Republic of South Africa - Greyling, Johannes Stephanus (University of the Free State, 1986)
As a study in the field of Comparative Education, the research deals with the patterns of provision of non-formal education which evolved as they developed in South Africa and the United Kingdom, influenced by historical factors. The problem of the relationship between non-formal education, formal education and the private sector is approached from the angle of identifying the relationships between the various providers of nfe, the legal and financial framework in which it is found, and the real centres of initiative and policy. It is postulated that government to a large extent directs the relationship through selective policy statements, legislation and finance. The study is restricted to proficiency non-formal education, that which can be classified as pre-vocational, job-entry and continuous retraining, particularly in the urbanised sector. In the theoretical analysis of non-formal education it was found that non-formal education is in general intended for education that is integral and direct. It was seen that traditionally non-formal education seems to be associated with stasis and negatively with differentiation. As differentiation in a society increases, the incidence, duration and frequency of formal education increases. Education tends to be mostly reactive rather than pro-active and the more complex a society is, the more extensive schooling becomes. Increased symbolization in a society expands the formalization of schooling and in almost all historical instances the emergence of the State as amode of political organisation has led to formalization of education. It was found that the relationship between formal education and non-formal education could be complementary (where non-formal education extends formal education), supplementary (where non-formal education is an application of formal education), replacement education (where non-formal education replaces formal education) or incorporating (where formal and non-formal education are incorporated in one system). It is possible to analyse the structures e.g. education, physical, administrative, etc, to classify the relationship further. Concerning the relationship between education and the world of work, it is possible for government to intervene at a number of points to modify the educational process, the work process and other factors. Different relationship (linkage) approaches are possible. The process-intensive and requirements intensive approaches of Ferrin and Arbeiter are used. The degrees of linkage according to Ferrin and Arbeiter, which range from separation through communication, participation, substitution to integration are applied to the countries studied. The Ferrin and Arbeiter classification of service functions along an authority continuum is used to establish government and the private sector involvement. The manpower development approach to policies which could influence the non-formal education, formal education and private sector relationships, is referred to and the characteristics of a modern training policy are identified. In the research undertaken it was found that in the United Kingdom the Government intervened selectively at different times to influence the control and co-ordination of training, the financing of training and to solve particular problems such as unemployment. The responsibility for training is said to be that of industry, but the initiative to get large scale training in particular areas going often comes from the Government. The Government's role increased through the establishment of the Manpower Services Commission which helped to co-ordinate training. The MSC then withdrew its control of training to leave it in an organised way to industry and commerce, to continue voluntary. The MSC influences the type of further education, 'Open Tech' education and mid-career (PICKUP) retraining. Through various schemes it influences the content of pre-vocational and secondary education. It was found that the nature of non-formal education and the relationship of nfe with the private sector and formal education are strongly influenced by the Government. In the case of the RSA it was established that separate legislation provides for non-formal education of the different race groups and that Government policy and legislation restricted non-formal education, in the proficiency area, for Blacks employed in white areas until 1981. The Government's policy in the period from 1922 to 1981 went through a complete circle as the restrictions imposed in 1922 were finally reversed in 1981. It was found that the Government, through selective legislation and finance, steers the relationship between non-formal education, formal education and the private sector. Concerning the future of nfe in the RSA, it was felt that an integrated system of education incorporating non-formal education, should be developed but that closer co-operation between the Department of Manpower, the education departments and the private sector in designing pre-vocational education was needed. Secondly the degree of linkage or transition from school to work through instruction on the nature of industry, industry/commerce work exposure similar to the UK should be developed to enable an open horizontal flow system of education to work. Career-long further training through technical colleges and an 'Open Technikon' approach should be developed. The Department of Manpower should work closely with the education departments to ensure a more meaningfully integrated national manpower plan and a school-industry-link group should be established to develop that relationship. The private sector has an increasingly important role to play in skill, as well as socio-economic development. Finally it would seem that, as in the UK, initiatives should be taken for large scale non-formal education programmes, such as basic education, pre-vocational training and mid-career re-training.
Thesis (D.Ed. (History and Comprative Education))--University of the Free State, 1986
Keywords: Education -- Suid Africa; Informal education -- South Africa; Education